Optimizing the Use of Rediset ® LQ as an Additive in Warm Mix Asphalt Technology - Irfan Irfan; Bambang Sugeng Subagio; Eri Susanto Hariyadi; Indra Maha (Jurnal Teknik Sipil, 2020)
The application of warm mix asphalt technology to reduce mixing and compaction temperatures has a weakness in decreasing the performance of mixture and is more sensitive to high temperatures. This is influenced by the type of additives and the warm mix asphalt technology used. The purpose of this study is to determine the optimum percentage of Rediset®LQ used and the amount of temperature drop in the type of Pen 60/70 asphalt mixture. Determination of the percentage of optimum use of the Rediset®LQ was carried out by using mixed workability analysis. The results of the warm mix asphalt test are then compared with the control HMA, the volumetric value that is close to the control HMA is considered to have equivalent workability. The variation of the use of the Rediset®LQ is 0.25% to 0.75% with a variation of the mixture temperature reduction of 15 ºC, 30 ºC, and 45 ºC. The results showed that the optimum percentage of using Rediset®LQ on asphalt pen 60/70 was 0.5% with a large reduction in mixing temperature and optimum compaction of 30 ºC. Evaluation of the resilient modulus value of the WMA mixture is equivalent to the HMA mixture at low, medium, and high temperatures. Based on the analysis, the Warm Mix Asphalt Concrete Binder Course with Rediset®LQ additive, also lower mixing and compaction temperature, is suitable for use on pavement layers.